Empty promises and other true cases [compact disc, unabridged] - Rule, Ann (Rule, Ann. Ann Rule's crime files, 2013)
In this unnerving collection drawn from her personal crime files, Ann Rule brilliantly dissects the convoluted love affairs that all too often end in violence. Expertly analyzing a shocking, headline-making case, Rule unmasks the deadly motives inside a seemingly idyllic marriage: a beautiful young wife, a rising star in America's top-ranked computer corporation, and a prosperous husband, the scion of a family building business.